Basawuik Kato Maelo Raso - Ririn Yunita; Desfiarni Desfiarni (SENDRATASIK UNP, 2021)
The creation of a dance work called "Basawuik Kato Maelo Raso" aims to create creative dance works and to train as well as to educate the creative power of a choreographer to prepare ideas through innovative movements as a communicative language in a dance work. Basawik Kato Maelo Raso(interlocked words and appeared feelings) dance work is a dramatic dance work which focuses on the daily life of Minangkabau youth. Basawik Kato Maelo Raso dance work is a dance work inspired by the social phenomena of community life in traditional ceremonies such as the inauguration of penghulu (leaders), the village official events, and wedding party. Batombe tradition has the meaning as a medium to express feelings of like or dislike to the opposite sex, and it has a different response in each society.